The economics of local food systems: a toolkit to guide community discussions, assessments and choices - Thilmany McFadden, Dawn, author; Conner, David, author; Deller, Steven, author; Hughes, David, author; Meter, Ken, author; Morales, Alfonso, author; Schmit, Todd, author; Swenson, David, author; Bauman, Allie, author; Goldenberg, Megan Phillips, author; Hill, Rebecca, author; Jablonski, Becca B. R., author; et al. (Colorado State University. Libraries, 2016)
As consumers across the Nation express a growing interest in a closer connection to their food producers—whether through access to more localized markets and/or shorter supply chains— cities and regions have begun to regard the expansion of local food marketing activities as a critical component of their economic development strategies. Rising demand for locally produced, source-identified, and differentiated food products has generated a plethora of new and spinoff businesses in many communities, which aim to increase the range of and accessibility to local food items for both retail and wholesale customers. In turn, this emergence of local food businesses has sparked a groundswell of financial support and interest from private foundations and public agencies on the assumption that the development of local food systems contributes to positive economic outcomes, especially with respect to local economic development and improved farm viability. Unfortunately, given the nascent nature of local food demand growth and the scarcity of available data, relatively few of these efforts have been guided by rigorous assessments. In response, the United States Department of Agriculture (USDA) has formed new initiatives and programs to develop new markets and support existing markets so that producers and their communities may leverage these new opportunities. Specifically, the USDA, Agricultural Marketing Service (AMS) has managed the Farmers Market Promotion Program (now expanded to the Local Foods Promotion Program), with great expectations of positive outcomes, but no standardized approach on how to evaluate market and economic outcomes. As a result, a team of regional economists and food system specialists were assembled through a project hosted by Colorado State University (CSU) to develop a Toolkit comprised of food system assessment principles and economic indicators a community may expect to share. Given the real-world projects, experiences, and applied research of the CSU-led team, the Toolkit is grounded in practices that are credible and useable within the economic development discussions guiding communities. The goal of this Toolkit is to guide and enhance the capacity of local organizations to make more deliberate and credible measurements of local and regional economic activity and other ancillary benefits.